PENGARUH KEJELASAN SASARAN ANGGARAN DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA ORGANISASI PERANGKAT DAERAH KABUPATEN GIANYAR - Gusti Ayu Ari Andriani; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
The performance of government agencies is a form of media to report the success or failure a government agency on the implementation of organizational goals and objectives. This study aims to see the influence variable of the Clarity of Budget Objectives and the Reporting System on the Performance Accountability of Government Agencies at Regionals Apparatus Organization (ODP) Gianyar Regency. This research was conducted using a survey method with a questionnaire instrument. The number of samples studied was 132 respondents using purposive sampling technique using criteria. Data analysis techniques used in this study include descriptive analysis, validity test, reliability test, classical assumption test, multiple linear analysis, f test, coefficient of determination (R2) and t test.